The efficacy of therapy with rituximab (R-CHOP) in patients with diffuse large cells lymphoma - T. D. Lutskaya; A. K. Golenkov; T. A. Mitina; I. V. Buravtsova; G. A. Dudina; L. L. Vysotskaya; E. V. Trifonova; E. V. Kataeva; O. V. Moskalets; V. V. Yazdovskiy (Онкогематология)
This study aimed to evaluate treatment results in patients with diffuse large cell lymphoma (DBL CL) received R-CHOP program (as 1 st and2 nd line therapy), including cases with complications. We observed 77 DBLCL patients (50 primary and 27 received other chemotherapy programs, in relapse, progression or treatment resistance phase). The median age is 54.1 years (21–79 years). 33 patients (43 %) had a high risk for unfavorable disease course according to IPI. Complications associated with development of severe compression syndromes, which required the appropriate surgical intervention, w as diagnosed in 45 (58.4 %) patients. From 50 primary patients received R-C HOP as the f irst line therapy objective treatment response was registered in 47 (94.0 %). Complete response was registered in 43 (86.0 %). The proportion of patients in whom response was maintained for 6 months w as 72.0 % in group with maintenance therapy and 28.0 % in group without it. These results were achieved when induction period density was 0.9. The last parameter is the ratio of the courses number to their time in mon ths. The density of standard induction R-C HOP-21 is 1.4. From 27 relapse or refractory patients received R-C HOP as the second line therapy objectivetreatment response was registered in 85.1 % of patients. Induction period density w as 1.03. The proportion of patients in whom response was maintained for 6 months was 74.0 %. Three classes serum Ig concentrations analysis before and after induction period in 16 pati ents showed normal values. With the median (Me) follow-up time in all patients over 24 months 3-years survival w as 93 % and Me w as not achieved. 3-years survival was 100 % in primary patients and 80 % in patients with previously treatment, and Me is also not achieved.